Doping in Paralympic sport: perceptions, responsibility and anti-doping education experiences from the perspective of Paralympic athletes and parasport coaches - Blank, Cornelia; Weber, Kathrin; Boardley, Ian D.; Abel, Thomas; Schobersberger, Wolfgang; Patterson, Laurie B. (Frontiers in Sports and Active Living, 2023)
Introduction Limited effort has been invested in understanding doping in Paralympic sport. The limited evidence that exists suggests that factors influencing doping in parasport are similar to Olympic sport. However, based on the design and nature of the previous studies, where methods have been mostly limited to qualitative data and prevalence numbers, further research is warranted to extend previous findings. Methods Informed by current evidence from Paralympic and Olympic sport, we aimed to investigate (1) para-athletes' perceptions of Anti-Doping Rule Violations (ADRVs) and responsibility for them, (2) descriptive norms for doping in parasport (3) perceptions of anti-doping education and legitimacy of anti-doping authorities, and (4) coach engagement in doping prevention and levels of doping confrontation efficacy using a quantitative survey approach. Results In total, valid survey responses from 126 Paralympic athletes and 35 coaches from four countries (Germany, Austria, Switzerland, UK) were analysed for experience with anti-doping, descriptive norms, anti-doping education, perceived legitimacy, knowledge, and doping confrontation efficacy (coaches only). Across both athletes and coaches, the level of education was generally good and doping willingness was low. Classification cheating was considered a form of doping and seems to be an important issue for athletes and coaches, especially within the UK sample. For 33.3% of the athletes, doping control was their first experience with anti-doping. Coaches' engagement with doping prevention activities and their perceived efficacy to confront doping-related matters appears to be higher compared to Olympic coaches' samples. Discussion Sport organisations/NADOs in Paralympic sport could use synergies with those organisations in Olympic sport, adopting similar approaches to anti-doping education, also focusing on a balanced communication of doping prevalence numbers and testing figures. Efforts to ensure athletes are educated about anti-doping before they are tested should be upheld. It seems that in para sport, different compared to able-bodied coaches, anti-doping organizations do not have to convince the coaches about their roles (i.e., being responsible for anti-doping education) anymore but can directly build on these resources. Overall, it seems that there are few differences between parasport and able-bodied sports and thus responsible organisations could use the existing programmes in Olympic sport and only adapt special content (e.g., boosting) which is unique to Paralympic athletes.